Simultaneous nitrification, denitrification and phosphorus recovery (SNDPr) - An opportunity to facilitate full-scale recovery of phosphorus from municipal wastewater - Salehi, Sara; Cheng, K.; Heitz, Anna; Ginige, M. (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2019)
Sewage treatment plants are a potential point source for recycling of phosphorus (P). Several technologies have been proposed to biologically recover P from wastewater. The majority of these technologies are side-stream processes and rely on an external source of soluble organic carbon to facilitate P recovery. To date, no studies have demonstrated the potential to facilitate main-stream recovery of P, using carbon that is naturally present in wastewater. Simultaneous nitrification, denitrification and phosphorus removal (SNDPR) is an elegant process that can uptake influent carbon and effectively remove both nitrogen (N) and P from wastewater. SNDPR studies to date, however, have failed to facilitate an end-of-anaerobic-phase P rich liquor, that enables economies of scale to recover influent P. Therefore, this study examined the feasibility of achieving a P rich liquor (e.g. > 70 mg-P/L) in a granular SNDPR process. A synthetic influent that replicated the nutrient and carbon concentrations of municipal wastewater was used to investigate whether carbon in the influent wastewater could enable both nutrient removal and P recovery from wastewater. Our granular SNDPR process was able to facilitate an end-of-anaerobic-phase liquor with P enriched to approximately 100 mg-P/L. A dissolved oxygen (DO) concentration of 0.5 mg/L in a sequencing batch reactor (SBR) was found to be essential to achieve complete nutrient removal and a high P concentration at the end of the anaerobic phase. At this steady state of reactor operation, the abundance of polyphosphate accumulating organisms (PAOs) was 2.6 times the abundance of glycogen accumulating organisms (GAOs). The study also demonstrated the importance of denitrifying polyphosphate accumulating organisms (DPAOs) and glycogen accumulating organisms (DGAOs) to achieve complete removal of N from the effluent. Compared to nitrifying bacteria, the polyphosphate accumulating organisms (PAOs) had a higher affinity towards DO. This study, for the first time, showed that the mainstream recovery of P is feasible using a SNDPR process.